1995
DOI: 10.1128/jvi.69.6.3639-3646.1995
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of feline immunodeficiency virus: classification of Japanese isolates into two subtypes which are distinct from non-Japanese subtypes

Abstract: and Aomori-2, were isolated from FIV-seropositive domestic cats in Japan, and their proviral DNAs were amplified by PCR. The nucleotide sequences of their env and gag genes were determined and compared with those of previously described isolates: U.S. and European isolates and one Japanese isolate, TM2. Phylogenetic analyses of complete env gene sequences demonstrate that worldwide isolates are classified into three subtypes: Japanese TM2, Japanese Shizuoka, and non-Japanese subtypes (U.S. and European isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(61 citation statements)
references
References 28 publications
2
57
1
1
Order By: Relevance
“…1) have been established based on phylogenetic analyses of sequences from the env V3-V5 region (Sodora et al, 1994;Kakinuma et al, 1995;Pecoraro et al, 1996). Recent papers have also used the gag gene to confirm the env clades (Kakinuma et al, 1995;Duarte et al, 2002;Steinrigl and Klein, 2003;Reggeti and Bienzle, 2004;Weaver et al, 2004;Hayward and Rodrigo, 2008). Subtypes A, B and C are most widespread worldwide, with subtype D only found in Japan and Vietnam (Kakinuma et al, 1995;Nakamura et al, 2003) and subtype E only found in Argentina (Pecoraro et al, 1996).…”
Section: Fiv-fca Subtypesmentioning
confidence: 99%
“…1) have been established based on phylogenetic analyses of sequences from the env V3-V5 region (Sodora et al, 1994;Kakinuma et al, 1995;Pecoraro et al, 1996). Recent papers have also used the gag gene to confirm the env clades (Kakinuma et al, 1995;Duarte et al, 2002;Steinrigl and Klein, 2003;Reggeti and Bienzle, 2004;Weaver et al, 2004;Hayward and Rodrigo, 2008). Subtypes A, B and C are most widespread worldwide, with subtype D only found in Japan and Vietnam (Kakinuma et al, 1995;Nakamura et al, 2003) and subtype E only found in Argentina (Pecoraro et al, 1996).…”
Section: Fiv-fca Subtypesmentioning
confidence: 99%
“…For application of RNAi technology to therapeutic purposes of naturally FIV-infected cats, sequence diversity of FIV genome should be considered. The sequence used for preparation of G4-siRNA, which efficiently inhibited the replication of FIV in this study, is highly conserved among various strains of FIV (Kakinuma et al, 1995). Therefore, it is highly plausible that the siRNA such as G4 inhibits the replication of various field strains of FIVas well as Petaluma strain.…”
Section: Discussionmentioning
confidence: 91%
“…The design of siRNAs was based on general guidelines (Elbashir et al, 2001). Four siRNAs (G1, G2, G3, and G4) corresponding to gag gene of Petaluma FIV14 (Olmsted et al, 1989) (GenBank accession number: M25381) were chosen from the highly conserved sequence of FIV gag gene (Kakinuma et al, 1995) and synthesized (Dharmacon Research, Lafayette, CO). An siRNA (Luc) corresponding to the coding sequence of firefly luciferase was purchased from Dharmacon Research and used as a control.…”
Section: Preparation Of Sirnasmentioning
confidence: 99%
“…FIV is present worldwide and can be classified into five well-characterised subtypes (A-E) [9][10][11][12][13]. The prevalence of FIV varies from 1% to 44%, depending on the health status of the investigated cats [3,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%